An assessment of service quality and resulting customer satisfaction in Pakistan International Airlines. Issue 5 (5th May 2015) - Ali, Faizan; Dey, Bidit Lal; Filieri, Raffaele
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to assess foreigners and overseas Pakistanis' evaluation of the quality of the services provided by Pakistan International Airlines (PIA) and its effect on customer satisfaction. Design/methodology/approach – A convenience sample of 498 respondents was used to test the hypotheses of the study through structural equation modelling. Findings – The results of this study indicate that all of the hypotheses are supported and customer satisfaction of PIA customers is influenced by all of the five service quality dimensions (AIRQUAL), including airline tangibles, terminal tangibles, personnel, empathy, and image. Research limitations/implications – This research examines the relationship between service quality dimensions and customer satisfaction. The study focuses on the evaluation of overseas Pakistanis and foreigners regarding the service quality of PIA. The main limitation of this study is that it focuses on PIA: thus, the results cannot be generalised. Practical implications – The results indicate that managers should focus on different dimensions of airline service quality in order to enhance customer satisfaction. Originality/value – This study would enable PIA to have a better understanding of the effects of service quality, which will lead to passengers' satisfaction and encourage the development of long-term relationships with their customers.